2021
DOI: 10.1016/j.csbj.2021.09.021
|View full text |Cite
|
Sign up to set email alerts
|

Transfer RNA-derived non-coding RNAs (tncRNAs): Hidden regulation of plants' transcriptional regulatory circuits

Abstract: Graphical abstract

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 71 publications
0
13
0
Order By: Relevance
“…These observations further suggested that tsRNAs are not random degradation products, but potential regulators during stress responses. Accumulating data showed that the expression of plant tsRNAs can be regulated by Pi starvation ( Hsieh et al., 2009 ; Hackenberg et al., 2013 ), heat stress ( Wang et al., 2016 ), UV treatment ( Cognat et al., 2017 ) and fungal infection ( Zahra et al., 2021 ; Gu et al., 2022 ; Sun et al., 2022 ), indicating the possible function of these tsRNAs in plant stress responses ( Table 1 ).…”
Section: Expression Of Tsrnas Under Stressesmentioning
confidence: 99%
“…These observations further suggested that tsRNAs are not random degradation products, but potential regulators during stress responses. Accumulating data showed that the expression of plant tsRNAs can be regulated by Pi starvation ( Hsieh et al., 2009 ; Hackenberg et al., 2013 ), heat stress ( Wang et al., 2016 ), UV treatment ( Cognat et al., 2017 ) and fungal infection ( Zahra et al., 2021 ; Gu et al., 2022 ; Sun et al., 2022 ), indicating the possible function of these tsRNAs in plant stress responses ( Table 1 ).…”
Section: Expression Of Tsrnas Under Stressesmentioning
confidence: 99%
“…Similarly, exosomal transfer RNAs (tRNA) have shown to be in greater amounts in patients of certain disease as compared to healthy individuals [ 14 ]. Nevertheless, the exact mechanism of tRNA fragments is uncertain, but they regulate some pathways and transfer components to other cells to be recognized [ 15 , 16 ]. In addition, PIWI-interacting RNAs (piRNAs) are one of the largest classes of noncoding RNA (ncRNA) molecules found in the extracellular environment and reside in EVs.…”
Section: Exosome Biologymentioning
confidence: 99%
“…In tandem with TEs, transfer RNAs also partake in the etiology of neurodevelopmental disorders ( Blaze and Akbarian, 2022 ). TEs have been associated with shorter transfer RNA-derived RNA fragments in plants ( Zahra et al, 2021 ), which are known to inhibit translation and modulate immune response ( Blaze and Akbarian, 2022 ). Therefore, this may be another avenue worth exploring for TE pathogenesis in developmental diseases and disorders.…”
Section: When Transposable Elements Go Awrymentioning
confidence: 99%